1996
DOI: 10.1007/s004360050157
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oocyst shedding and the serum immune response to Cryptosporidium parvum in cattle and pigs

Abstract: A comparison was made between oocyst shedding and the presence of specific serum IgG antibodies to Cryptosporidium parvum in 108 bovines and 90 pigs. Oocysts were detected by a commercial immunofluorescence assay in feces from 26.8% of bovines and 34.4% of pigs, whereas positive titers as determined by an indirect fluorescent antibody method were found in sera from 12.9% and 48.9% of the respective animals. Infection was significantly most frequent in suckling calves (82.7%) and weaned piglets (87.5%). By cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The youngest age of C. parvum we detected was 7 days, which is in concordance with previous reports that calves get infected with this parasite within the first 1 to 2 days of life and start shedding oocysts after a 5 to 6 days before patent period (Castro-Hermida et al 2002b;Ongerth and Stibbs 1989;Quilez et al 1996). The youngest calf shedding C. bovis and C. ryanae oocysts was 10 and 22 days of age, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The youngest age of C. parvum we detected was 7 days, which is in concordance with previous reports that calves get infected with this parasite within the first 1 to 2 days of life and start shedding oocysts after a 5 to 6 days before patent period (Castro-Hermida et al 2002b;Ongerth and Stibbs 1989;Quilez et al 1996). The youngest calf shedding C. bovis and C. ryanae oocysts was 10 and 22 days of age, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, no signs of clinical illness were seen in either new-born or weaned miniature piglets repeatedly inoculated with 10 6 to 10 7 C. parvum oocysts (Arnault et al, 1994). Neither were any clinical manifestations observed in experimentally infected piglets older than 15 days (Tzipori et al, 1982), and isolation studies as well as epidemiological surveys have shown that oocyst shedding was not statistically associated with diarrhoea in naturally infected pigs from conventional farms (Sandford, 1987;Quilez et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…New developments in molecular biology make PCR-based diagnostics promising for the future, particularly when genotyping is warranted, but at the present time they are not developed for use in rapid diagnosis at the population level. Development and validation of an enzyme linked immunosorbant assay (ELISA) for serum could fulfil the needed criteria because anti-Cryptosporidium antibodies have been detected which can persist longer than oocysts are shed (Whitmore and Harp 1991;Lorenzo-Lorenzo et al 1993;Quilez et al 1996).…”
Section: Introductionmentioning
confidence: 99%